The impact of COVID-19 in children post hematopoietic stem cell transplantation: Experience from a pediatric transplant unit in India - Rumesh Chandar; Venkateswaran Vellaichamy Swaminathan; Satishkumar Meena; Harika Varla; Ramya Uppuluri; Revathi Raj (Elsevier, 2022)
Introduction: Hematopoietic stem cell transplantation (HSCT) has been particularly challenging during the COVID-19 pandemic. We aimed to analyse the impact of infection with COVID-19 in children post-HSCT and describe the clinical syndromes and the disease manifestations in this cohort. Patients and methods: Children who underwent HSCT between January 2019 to June 2021 and acquired COVID-19 infection were included in the study. The symptomatic children were hospitalized for supportive care. Asymptomatic children were treated in home isolation with azithromycin and zinc supplements. Children who were on immunosuppressants were continued on it. Results: A total of 9/265 children who underwent HSCT in the study period were diagnosed with COVID-19, the incidence being 3.3%. The cycle threshold value in all children was low (≤17), indicating a profound viremia. All children had cytopenia, four had hyponatremia, and two had grade 2 cytokine release syndrome. The severity of the disease was mild in 5 children, moderate in 1 child, and severe in 3 children. Post COVID sequelae included ARDS (n = 1), MIS-C and DVT (n = 1), rhinocerebral rhizopus infection (n = 1). Three children with severe infection died, two due to multiorgan dysfunction and one due to fungal infection. Conclusion: The presence of GVHD, opportunistic fungal infection, and hyponatremia help predict a severe course and mortality in children post HSCT who are diagnosed to have COVID-19 infection. Prophylaxis for mucormycosis in high-risk children with GVHD is an essential aspect of management.